PRINCIPLES FOR FORMING A HEALTHY HOUSING ENVIRONMENT AS A COMPONENT OF SALUTOGENIC DESIGN - САМОЙЛОВИЧ, В. В.; Юнаков, С. Ф. (Art and Design, 2022)
The purpose of the publication is to determine the principles for the formation of a healthy living environment through the development of architectural and design components of the design of ecological cities. Methodology. Research methods are based on the principles of a systematic approach in the analysis of factors affecting the population in an urban environment. Research results. Based on the analysis of regulatory documents and literary sources on the theory and practice of the formation of a healthy living environment, as well as the climatic and urban conditions for the formation of ecological cities, the main principles for the formation of the components of the residential environment, which include not only a comfortable living space, a house and an adjacent the territory, as well as the urban natural environment, the transport system of the residential area, the district infrastructure, etc. Examples of the most optimal solutions based on international experience in the formation of a healthy living environment are given. The scientific novelty of the work lies in determining the principles of salutogenic design for their application in the conditions of Ukraine, which creates a comfortable living environment and contributes to the social organization of people that ensure the preservation and strengthening of their health. Practical significance. The results of the work can be used in the practical activities of architects, designers and students of educational institutions of this specialization.